Struktur Komposisi dan Estimasi Cadangan Karbon Tegakan Ekosistem Mangrove di Pulau Sangiang, Banten - Wiwid Andriyani Lestariningsih; Muhamad Gilang Arindra Putra; Aulia Rahmania Putri; Budi Prabowo; Fadel Muhammad; Prakas Santoso; Cakra Adiwijaya; Idris; Wahyu Ayu Setyaningsih; Dea Fauzia Lestari; Neviaty Putri Zamani (Program Studi Ilmu Kelautan, Jurusan Perikanan dan Ilmu Kelautan, Fakultas Pertanian, Universitas Mataram, 2022)
The mangrove ecosystem is a coastal ecosystem that is important for humans. Mangroves absorb carbon in the atmosphere and store it in biomass or sediment. So, in other words, mangroves play a significant role in mitigating global climate change. This study aimed to examine the structure of the mangrove ecosystem composition and estimate standing carbon stocks on Sangiang Island, Banten. The data taken was for the categories of trees, saplings, and seedlings (consisting of mangrove species, DBH, and height). The study was conducted at three stations with three replications for each station. The allometric formula obtained the estimated carbon stock from the stand biomass value. The results showed that 11 species of mangrove species were found with an average density of 1266 ind/ha (trees), 3733 ind/ha (saplings), and <70% (seedlings). Then the estimated average carbon stock in Sangiang Island, Banten is 271.29 tons/ha.